Conceptualización del riesgo en los mercados financieros (Foro: Revista de Derecho, 2017)
El riesgo está inmerso en todas las actividades humanas y es entendido como la probabilidad de ocurrencia de un evento que deviene en un perjuicio. Por ende al hablar de riesgo en materia financiera, nos referimos a una eventual pérdida de dinero que signifique, de manera directa, una afectación al sistema financiero o a una de las instituciones que lo conforman. Con lo antedicho, el presente trabajo consiste en una recopilación de información de algunos de los riegos inmersos en los mercados financieros. Con ello, la exposición de riesgos como los de mercado, operacional, de liquidez, legal, reputacional, entre otros, resulta fundamental. Finalmente hemos optado por presentar, en breves rasgos, algunos de los riesgos de crédito y métodos válidos para su adecuada valoración.Risk is the probability of an event and its consequencesH.l Despite the frequency of the use of the term risk there is not formal definition for it. Therefore, common understanding of the term has an inherent subjective character. When we talk about risk with reference to specific organizations it may be defined as an effect of the existing uncertainty in such organizations which may consist of a negative effect or a deviation from the proposed goals. When this aforementioned goal is of a financial nature is when financial risk is present. The above definition is specified in two statements: 1) Financial risk is an event that has not yet occurred and upon which uncertainty exists. 11) The occurrence of an event would have negative (losses) impacts (financial). Departing somewhat from the subjective definitions and getting closer to the regulations on the subject of risk, it should be seen as ""the result of a combination of the probability of an event and its financial impact (loss in monetary units).